2022
DOI: 10.3390/ijerph19159572
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Risk Assessment of Dietary Exposure to Cadmium in Residents of Guangzhou, China—Young Children Potentially at a Health Risk

Abstract: Cadmium (Cd) and its compounds are hazardous environmental pollutants with renal toxicity and human carcinogenicity, with ingestion of contaminated foods representing the major mode of exposure. There have been a number of reports evaluating the Cd content in various foods; however, regarding the actual risk posed by dietary cadmium exposure, only a few reports are available in which single point evaluation (less accurate than multiple point evaluation) was employed. In this study, we used a margin of exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Our results are consistent with the exposure assessment in the adult population and preschool children in the Republic of Serbia [ 53 ]. A risk assessment of dietary Cd exposure to Cd in residents of Guangzhou demonstrated that young people had lower margin of exposure (MOE) values (0.92) and indicated a higher risk, while those for the other age groups were all above 1.0 [ 18 ]. Additionally, young children and infants may be exposed to more Cd because they eat more food than is needed to maintain their weight (to realize growth and development), and therefore, Cd is more absorbable for them than adults [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with the exposure assessment in the adult population and preschool children in the Republic of Serbia [ 53 ]. A risk assessment of dietary Cd exposure to Cd in residents of Guangzhou demonstrated that young people had lower margin of exposure (MOE) values (0.92) and indicated a higher risk, while those for the other age groups were all above 1.0 [ 18 ]. Additionally, young children and infants may be exposed to more Cd because they eat more food than is needed to maintain their weight (to realize growth and development), and therefore, Cd is more absorbable for them than adults [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other standards worldwide, the food limits of Cd are 0.005–3 mg/kg in the European Union, 0.05–2.5 mg/kg in Australia, and 0.003–2 mg/kg in the international Codex Alimentarius Commission (CAC), respectively. A health risk assessment in China’s Guangdong Province indicated that rice grain, leaf vegetables, bivalves, and shrimp and crabs were the main contributors of Cd exposure [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium is a widely used toxic metal in industry and agriculture, including cigarette, battery production, fossil fuel burning and fertilizers [23][24][25]. Due to the long biological half-life and the low excretion rate, cadmium could thus accumulate in human body and cause a lot of disease [3].…”
Section: Discussionmentioning
confidence: 99%